Education to Improve the Working Posture With the Rula Method to Reduce Musculoskeletal (Case study: Grain takers in waluya village, karawang) - Al Qohar, Muhammad Fikri Bivani; Wibowo, Enrique; Rizky, Muhammad; Wahyudin, Wahyudin; Herwanto, Dene; Nugraha, Asep Erik (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
The Farmers in the village of Waluya, Kutawaluya district, Karawang District, Farmers complain about musculoskeletal injuries because of the routine of cooking every day, where farmers work with the body posture bending so that they have some problems such as waist pain to the bump bending.Â Â  Focus on the health of the posture of the farm worker, it is necessary to have a measurement of the body posture using the method of Rapid Upper Limb Assessment (RULA). After being analyzed with the method RULA. Posture of farm workers yields a score of 7 points, which means that the farm workers need to have an action and improvement such as feeding facilities such as Kitchenware or taking the remnants of the falling or untransported crop, so that farm workers feel comfortable.